2016
DOI: 10.1158/0008-5472.can-16-0587
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Adoptive T-cell Therapy Is Improved by Treatment with the Antioxidant N-Acetyl Cysteine, Which Limits Activation-Induced T-cell Death

Abstract: While adoptive transfer of autologous tumor antigen-specific T cell immunotherapy can produce remarkable clinical efficacy, most patients do not achieve durable complete responses. We hypothesized that reducing susceptibility of T cells to activation-induced cell death (AICD), which increases during the rapid in vitro expansion of therapeutic T cells before their infusion, might improve the persistence of adoptively transferred cells. Our investigations revealed that repetitive stimulation of the T cell recept… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 54 publications
(63 reference statements)
1
38
0
Order By: Relevance
“…Recent study has shown that central memory T cells with higher cytosolic glutathione, surface thiol, and intracellular antioxidant levels survive longer in tumor and control tumor growth than effector memory T cells with less antioxidant levels and that treatment with antioxidants improved the function of tumor-infiltrating T lymphocytes (TILs), leading to prolonged survival of patients receiving these treated TIL. 102 Further work is warranted to determine if this system could be broadly used to discover such a combination parameter of NIR lasers.…”
Section: Discussionmentioning
confidence: 99%
“…Recent study has shown that central memory T cells with higher cytosolic glutathione, surface thiol, and intracellular antioxidant levels survive longer in tumor and control tumor growth than effector memory T cells with less antioxidant levels and that treatment with antioxidants improved the function of tumor-infiltrating T lymphocytes (TILs), leading to prolonged survival of patients receiving these treated TIL. 102 Further work is warranted to determine if this system could be broadly used to discover such a combination parameter of NIR lasers.…”
Section: Discussionmentioning
confidence: 99%
“…Based on enhanced oxidative stress, our data indicate that excessive PDI-ERO1α activity may undermine glutathione homeostasis in effector T cells. These data are important in the context of cancer immunotherapy, because maintenance of the reduced glutathione pool is essential for T cell tumor control [45] and inflammatory responses [46,47]. The specific role of PDI-ERO1α relay to shape glutathione homeostasis in T cells is an area of interest.…”
Section: Discussionmentioning
confidence: 99%
“…T cell populations expand considerably upon antigenic stimulation, followed by a period of contraction as cells targeting self-antigens are deleted. Clonal deletion presents a technical barrier for adoptive cell therapies that use T cells with tumor antigen-specific TCRs or engineered TCRs by affecting both developing and mature T cells [126,127] .…”
Section: Suppressive Factors In the Tmementioning
confidence: 99%
“…Caspase-dependent AICD relies on the interaction between Fas-expressing T cells and FasL-expressing tumor cells to trigger a caspase cleavage cascade within the T cell, leading to apoptosis [128] . Caspase-independent AICD occurs upon repetitive TCR stimulation and c-JUN N-terminal kinase activation, which triggers the release of mitochondria-derived death effectors [126,127,129] . p53 may also contribute to a mitochondria-centric cell death by activating a DNA damage response pathway consisting of DNA damage marker γH2AX upregulation and ATM activation [127] .…”
Section: Suppressive Factors In the Tmementioning
confidence: 99%
See 1 more Smart Citation